Antimicrobial resistance in Clostridioides (Clostridium) difficile derived from humans: a systematic review and meta-analysis - Sholeh, Mohammad; Krutova, Marcela; Forouzesh, Mehdi; Mironov, Sergey; Sadeghifard, Nourkhoda; Molaeipour, Leila; Maleki, Abbas; Kouhsari, Ebrahim (Antimicrobial resistance and infection control, 2020)
BACKGROUND: Clostridioides (Clostridium) difficile is an important pathogen of healthcare- associated diarrhea, however, an increase in the occurrence of C. difficile infection (CDI) outside hospital settings has been reported. The accumulation of antimicrobial resistance in C. difficile can increase the risk of CDI development and/or its spread. The limited number of antimicrobials for the treatment of CDI is matter of some concern. OBJECTIVES: In order to summarize the data on antimicrobial resistance to C. difficile derived from humans, a systematic review and meta-analysis were performed. METHODS: We searched five bibliographic databases: (MEDLINE [PubMed], Scopus, Embase, Cochrane Library and Web of Science) for studies that focused on antimicrobial susceptibility testing in C. difficile and were published between 1992 and 2019. The weighted pooled resistance (WPR) for each antimicrobial agent was calculated using a random- effects model. RESULTS: A total of 111 studies were included. The WPR for metronidazole and vancomycin was 1.0% (95% CI 0-3%) and 1% (95% CI 0-2%) for the breakpoint > 2 mg/L and 0% (95% CI 0%) for breakpoint ≥32 μg/ml. Rifampin and tigecycline had a WPRs of 37.0% (95% CI 18-58%) and 1% (95% CI 0-3%), respectively. The WPRs for the other antimicrobials were as follows: ciprofloxacin 95% (95% CI 85-100%), moxifloxacin 32% (95% CI 25-40%), clindamycin 59% (95% CI 53-65%), amoxicillin/clavulanate 0% (0-0%), piperacillin/tazobactam 0% (0-0%) and ceftriaxone 47% (95% CI 29-65%). Tetracycline had a WPR 20% (95% CI 14-27%) and meropenem showed 0% (95% CI 0-1%); resistance to fidaxomicin was reported in one isolate (0.08%). CONCLUSION: Resistance to metronidazole, vancomycin, fidaxomicin, meropenem and piperacillin/tazobactam is reported rarely. From the alternative CDI drug treatments, tigecycline had a lower resistance rate than rifampin. The high-risk antimicrobials for CDI development showed a high level of resistance, the highest was seen in the second generation of fluoroquinolones and clindamycin; amoxicillin/clavulanate showed almost no resistance. Tetracycline resistance was present in one fifth of human clinical C. difficile isolates.
Keywords: Drug Resistance, Bacterial; antibakteriální látky; fluorochinolony; Microbial Sensitivity Tests; Clindamycin; Clostridioides difficile; Clostridium Infections; Metronidazole; Vancomycin; klostridiové infekce; Antimicrobial resistance; lidé; Anti-Bacterial Agents; Fluoroquinolones; klindamycin; Humans; bakteriální léková rezistence; mikrobiální testy citlivosti; Meta-analysis